How Financial Conditions Matter Differently across Latin America - Brandao Marques, Luis (IMF Working Papers; Working Paper ;, 2017)
This paper develops comparable financial conditions indices (FCIs) for the six large and most financially-integrated Latin American economies (LA6) by following Korobilis (2013) and Koop and Korobilis (2014). The main findings are as follows. First, the estimated FCIs are influenced by a commodity cycle, a global financial cycle, as well as country-specific episodes of financial distress. Second, by early 2017, financial conditions remained favorable in most LA6 economies relative to historical standards. Third, the impact of financial shocks on economic activity widely varies across LA6 and is otherwise found to be stronger in periods of financial stress. Fourth, exposure to regional financial spillovers also differs across LA6.